Biochemical characterization and crystal structure of a GH10 xylanase from termite gut bacteria reveal a novel structural feature and significance of its bacterial Ig‐like domain. Issue 12 (9th July 2013) - Han, Qian; Liu, Ning; Robinson, Howard; Cao, Lin; Qian, Changli; Wang, Qianfu; Xie, Lei; Ding, Haizhen; Wang, Qian; Huang, Yongping; Li, Jianyong; Zhou, Zhihua
Abstract Bacterial Ig‐like (Big) domains are commonly distributed in glycoside hydrolases (GH), but their structure and function remains undefined. Xylanase is a GH, and catalyzes the hydrolysis of the internal β‐xylosidic linkages of xylan. In this study, we report the molecular cloning, biochemical and biophysical characterization, and crystal structure of a termite gut bacterial xylanase, Xyl‐ORF19, which was derived from gut bacteria of a wood‐feeding termite (Globitermes brachycerastes). The protein architecture of Xyl‐ORF19 reveals that it has two domains, a C‐terminal GH10 catalytic domain and an N‐terminal Big_2 non‐catalytic domain. The catalytic domain folds in an (α/β)8 barrel as most GH10 xylanases do, but it has two extra β‐strands. The non‐catalytic domain is structurally similar to an immunoglobulin‐like domain of intimins. The recombinant enzyme without the non‐catalytic domain has fairly low catalytic activity, and is different from the full‐length enzyme in kinetic parameters, pH and temperature profiles, which suggests the non‐catalytic domain could affect the enzyme biochemical and biophysical properties as well as the role for enzyme localization. This study provides a molecular basis for future efforts in xylanase bioengineering. Biotechnol. Bioeng. 2013;110: 3093–3103. © 2013 Wiley Periodicals, Inc.